Application of Green Mussel Shell Waste (Perna viridis) to the Growth and Production of Celery (Apium graveolens) - Elfarisna Elfarisna; Erlina Rahmayuni; Nur Oktavia; Welly Herman (CV. Truly Science Publishing, 2025)
Background: Green mussel shell waste (GMS) is a nutrient source that can be applied to celery plants. This study aimed to assess the potential of green mussel shell waste as a natural ameliorant that can improve soil fertility and support celery growth and production. Methods: The study was conducted from January to April 2022 at the experimental garden of the Faculty of Agriculture, Muhammadiyah University of Jakarta. The study used a Randomized Complete Block Design (RCBD) with five treatments: inorganic fertilizer (control), GMS waste 4 g/plant, GMS waste 8 g/plant, GMS waste 12 g/plant, and GMS waste 16 g/plant . Results: The results showed that the use of GMS waste increased soil pH from acidic (6,13) to neutral (6.63-7.33), particularly at doses of 12 g and 16 g per plant. Despite this, inorganic fertilizers provide the best results in terms of plant growth, particularly in terms of plant height, number of leaf stalks, and fruit weight. Conclusion: GMS waste shows potential as an alternative fertilizer, but its effectiveness in supporting celery plant growth is still limited, due to its incomplete nutrient content and slower nutrient release compared to inorganic fertilizers.